Ultrasonic Study of Binary Mixture of N-Butyl Alcohol and Aniline at Room Temperature (International Journal of Scientific Research in Science and Technology, 2024)
Density (r) and viscosity (h) have been calculated for n-Butyl Alcohol, Aniline and  their binary mixtures at room temperature. Ultrasonic Velocity (U) have been  measured for pure liquids and their binary mixtures using Ultrasonic  interferometer at 2MHz frequency. Experimental data have been used to calculate  some derived parameters such as adiabatic compressibility (b), acoustical impedance (Z), relaxation time (t), free length () and free volume (). Also the excess parameters such as excess ultrasonic  velocity DU, excess  acoustical impedance (DZ), excess  relaxation (Dt), excess free length (D) and excess free volume (D These parameters have  been evaluated and discussed in light of intermolecular interaction in these  mixtures.
Keywords: Ultrasonic Velocity; Acoustic Parameters; Excess Parameters